Development of all-fiber laser intracavity with tapered biosensor - Mansor, Maisarah (2019)
The development of biosensors based on tapered optical fibers has shown promising results of high sensitivity and specificity. The sensing principle lies within the reaction of evanescent field driven from the tapering of the optical fiber extends into the surrounding medium and is highly sensitive to any changes in the refractive index within the vicinity of the tapered optical fiber, making it suitable to be used as a sensor. Recently, single mode tapered fiber has attracted great attention from researchers due to its high sensitivity and power-independent spectral measurements. However, the complexity of analyzing the multi-fringe optical spectrum makes it prone to misinterpretation. This research work demonstrates the integration of a bio-functionalized tapered fiber sensor in a fiber laser cavity for detection of biological molecules. The significance of integrating the sensor within the fiber laser cavity lies in the simplification of the sensing results. To ensure that the taper profile can maintain a single wavelength output during measurements, different taper profiles were tested with varying concentration of sodium chloride (NaCl) and taper profile with 15 μm waist diameter and waist length of 10 mm was found to be the best. Subsequently, tapered fiber using the optimum taper profile was functionalized with biotin and its sensing performance in ring cavity EDFL setup was then assessed by immersing the tapered fiber biosensor into various concentration of avidin ranging from 1 to 10 pM at the maximum pump power of 200 mW. The proposed setup obtained a sensitivity of 1.02 nm/pM with a detection limit of 1 pM. Afterwards, the bio-functionalized tapered fiber in ring cavity EDFL setup was tested at lower gain condition of 40 mW pump power, which yielded lower sensitivity of 0.4 nm/pM. The sensitivity value deteriorated at low gain condition since the net gain bandwidth was narrower and evanescent field interaction was affected by lower intensity light intensity in the cavity. The realization of a properly packaged all-fiber laser intracavity taper biosensor can simplify the analysis, translating the results in a single wavelength manner that is more practical without compromising the many qualities of this technology.